Biopsychosocial Variables in Male Schizophrenic Patients: A Comprehensive Comparison with Healthy Controls - Krzysztof Krysta; Beata Trędzbor; Ewa Martyniak; Aleksandra Cieślik; Agnieszka Koźmin-Burzyńska; Katarzyna Piekarska-Bugiel; Katarzyna Skałacka; Rafał Bieś; Marek Krzystanek (MDPI AG, 2023)
Objective: this study aims to comprehensively compare neuropsychological, psychopathological, anthropometric, biochemical, pharmacological, and lifestyle variables between 27 male schizophrenic patients (SZ group) and 30 age- and sex-matched healthy male controls (HC group). Methods: participants underwent a battery of neuropsychological tests including the Trail Making Test (TMT), Stroop Color-Word Interference Test, and Verbal Fluency Test. Psychopathological symptoms in the SZ group were evaluated using the Positive and Negative Syndrome Scale (PANSS). Anthropometric measurements such as body weight, height, BMI, and waist circumference were taken. Biochemical markers measured included fasting glucose, total cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and fasting insulin. Lifestyle factors were assessed through a questionnaire for the study of views and eating habits of people aged 16 to 65. Results: the HC group outperformed the SZ group in the TMT_A test and the Stroop test, but no significant differences were observed in the TMT_B test or in phonemic fluency tests. No correlation was found between age and PANSS scores within the SZ group. Anthropometrically, the SZ group had higher body weight, waist circumference, and BMI, with no difference in height. Biochemically, the HC group had higher HDL cholesterol levels but lower insulin and insulin resistance indices. Pharmacological assessment showed a more significant impact on body weight among SZ patients taking second-generation antipsychotics. Lifestyle factors such as diet and screen time were comparable between groups, but the SZ group reported longer sleep duration and lower leisure time activity. Conclusions: our study highlights distinct neuropsychological, pharmacological, anthropometric, and biochemical differences between male schizophrenic patients and healthy controls. The results underscore the complexity of schizophrenia and point toward the need for a multi-faceted approach to its management and understanding.